OPTIMALISASI PERAN KANTOR URUSAN AGAMA (KUA) DALAM MENANGANI PERMASALAHAN WALI ADHAL DI KECAMATAN SALAHUTU - Afrizal Hamid; Husin Anang Kabalmay; Thalhah; La Jamaa; Sahur Ramsay (IAIN Ambon, 2025)
Marriage guardianship is a fundamental pillar of Islamic marriage, guaranteeing the validity of the contract and protecting women's rights. In practice, the rejection of guardianship without Islamic justification (wali adhal) still occurs, hindering the implementation of marriages. This study aims to analyze the factors causing guardianship and the role of the Religious Affairs Office (KUA) in handling it in Salahutu District, Central Maluku Regency. This study used a qualitative method with a field research approach. Data were obtained through observation and interviews with Salahutu District Religious Affairs Office employees, lineage guardians, affected couples, and community leaders, supported by literature review. Data analysis was conducted using the Miles and Huberman interactive model. The results indicate that guardianship is influenced by internal family conflict, psychological trauma, guardian ego, demands for customary property (bokah), and the guardian's lack of understanding of legal and religious consequences. The Salahutu District KUA plays an active role as a non-litigation mediator through a persuasive approach and personal assistance, thereby resolving most cases without going through the courts and preventing unregistered marriages. Keywords: Islamic family law, religious affairs office, guardian adhal, marriage guardian